Elevated CO2 affects secondary metabolites in Robinia pseudoacacia L. seedlings in Cd- and Pb-contaminated soils. (October 2016) - Jia, Xia; Zhao, Yonghua; Liu, Tuo; Huang, Shuping
Abstract: Secondary metabolites play important roles in plant interactions with the environment. The co-occurrence of heavy metal contamination of soils and rising atmospheric CO2 has important effects on plant. It is important to explore the ways in which production of plant secondary metabolites is affected by heavy metals under elevated atmospheric CO2 . We examined the effects of elevated CO2 on secondary metabolite contents in Robinia pseudoacacia seedlings grown in Cd- and lead (Pb)-contaminated soils. The increase in secondary metabolites was greater under Cd + Pb exposure than under exposure to individual metals regardless of elevated CO2 with the exception of condensed tannins in leaves and total alkaloids in stems. Except for phenolic compounds and condensed tannins, elevated CO2 was associated with increased secondary metabolite contents in leaves and stems of plants exposed to Cd, Pb, and Cd + Pb compared to plants exposed to ambient CO2  + metals. Changes in saponins in leaves and alkaloids in stems were greater than changes in the other secondary metabolites. Significant interactive effects of CO2, Cd, and Pb on secondary metabolites were observed. Saponins in leaves and alkaloids in stems were more sensitive than other secondary metabolites to elevated CO2  + Cd + Pb. Elevated CO2 could modulate plant protection and defense mechanisms in R. pseudoacacia seedlings exposed to heavy metals by altering the production of secondary metabolites. The increased Cd and Pb uptake under elevated CO2 suggested that R. pseudoacacia may be used in the phytoremediation of heavy metal-contaminated soils under global environmental scenarios. Highlights: Secondary metabolites mediate plant interactions with the environment. Heavy metal contamination of soils co-occurs with elevated atmospheric CO2 . Elevated CO2 affects production of secondary metabolites in metal polluted soils. Saponins in leaves and alkaloids in stems are sensitive to elevated CO2  + Cd + Pb. Elevated CO2 was associated with greater Cd and Pb uptake by R. pseudoacacia.